The influence of merger and convection on an anticyclonic eddy trapped in a bowl. (November 2021) - de Marez, Charly; Le Corre, Mathieu; Gula, Jonathan
Abstract: We investigate the impact of several parameters on the lifecycle of an anticyclonic eddy lying in a topographic depression (a bowl), similar to the Lofoten Vortex and the Rockall Trough eddy cases. We observe that the vortex merger with submesoscale coherent vortices generated at depth allows the eddy to grow in size, and intensify at depth. Wintertime convection is also shown to directly intensify the eddy by deepening isopycnals. Also, convection indirectly affects the shape of the eddy. It enhances the number of merger (1) at the surface, with small vortices generated in the convectively-deepened surface mixed-layer, and (2) at depth, because the vertical distance between the main eddy's core and small companion vortices is reduced, thus increasing the merging efficiency. These processes altogether contribute to the maintaining of the eddy. On the other hand, the bottom drag is the main process contributing to the decay of the eddy. Our study thus shows that the sustaining for several years of such eddies trapped in a bowl is mainly due to the balance between merger and bottom drag. Highlights: Anticyclonic eddies lying in a topographic depression live for several years. Small SCVs generated nearby the anticyclonic eddy intensify the latter at their depth of generation. Wintertime convection is efficient in intensifying the anticyclonic eddy. The sustaining for several years of such eddies is due to the balance between merger, convection, and bottom drag.